Effects of gradient and age on energy expenditure and fat metabolism during aerobic exercise at equal intensity in women - Ahn, Ha-Na; Lee, Man-Gyoon; Jung, Won-Sang (Physical activity and nutrition, 2022)
[Purpose] This study aimed to investigate the effects of gradient and age on energy expenditure and fat metabolism during aerobic exercise at equal intensity in women.[Methods] Thirty women in their twenties (n=15) and fifties (n =15) were enrolled. All subjects performed aerobic exercise on a treadmill for 10 min at 0% and 6% gradient repeatedly to elicit 50%, 60%, and 70% VO2max.[Results] Energy expenditure and fat oxidation were higher during aerobic exercise at 6% of the gradient than at 0%, and there was no significant difference in carbohydrate oxidation in any age group.[Conclusion] Aerobic exercise at a 6% gradient was more favorable for fat oxidation than a 0% gradient in all age groups. In particular, in the case of women in their fifties, walking on a gradient of 6%, which is favorable for increasing fat oxidation, was more effective than walking on flat ground for preventing and reducing obesity. However, to examine the difference in fat oxidation among exercise intensities more accurately, exercise performed for longer than 30 min is required. Follow-up studies are required to investigate the effect of various gradients on physiological and metabolic characteristics when carrying out aerobic exercises for more than 30 min.